The perspective ofschool-based Occupational Therapy intervention toenhance the participation of learners with specialeducational needs in school activities - Harutyunyan, Zaruhi; Hovyan, Gohar
The aim of this study was to investigate the participation problems in school activities of the learners with special educational needs in order to establish the possible ways of Occupational Therapy intervention in school settings in Armenia. In total 111 learners with special educational needs were observed and their participation in educational and non-educational activities was assessed using the "Occupational Therapy School Skills Assessment'' tool. Since the educational environment considered being crucial for the learners’ participation, the school environment was observed to determine the features facilitating or burdening their involvement in all kinds of school activities. Quantitative research methodology was used to outline and summarize the participation problems of learners with special educational needs for establishing the possible ways of Occupational Therapy intervention. The results of this study highlighted that in the inclusive school in Armenia the learners with special educational needs still had participation restriction and their involvement in educational and non-educational activities was limited due to lack of individual skills and abilities, as well as not adapted environmental conditions. Learners with physical dysfunctions (62%) experienced mobility problems and had significant difficulties performing self-care activities, about 65% were not able to take part in outdoor events, permanent support and assistance were required. For the learners with autistic spectrum disorder (50%) communication with peers and staff members was still challenging and participation in the educational process was not effective.
Keywords: Education